Big Data and Its Impact on Research Methodology - Kumari, Pilli Lalitha; Yekula, Prasanna Kumar (AG Volumes, 2025)
The integration of information systems research and social sciences enables a new era of innovation. In this context, the social sciences are provided with new insights through the implementation of Big Data and analytics technology. It also provides innovative, adaptable solutions to critical social issues and obstacles. This article offers a thorough analysis of the wide range of literature on big data and how it affects research technique. It concluded that big data is reshaping research methodology by enabling access to vast datasets, novel analytical techniques, and dynamic data visualization tools. It fosters deeper understanding across disciplines, offering transformative potential in areas like customer behavior and sport management. However, effective application requires context-aware methods, high-quality data, and rigorous preprocessing. Conceptual frameworks assessing organizational readiness for big data adoption further enhance decision-making capabilities. As research evolves, big data’s value lies in its ability to generate responsive, socially aware insights. With appropriate methodologies and a focus on data integrity, big data continues to revolutionize research and knowledge creation across domains.